Meninjau Komitmen Indonesia Melarang Senjata Tertentu dalam Konflik menurut Hukum Humaniter Internasional - Raka, Maria Wilhelsya Inviolata Watu (Kajian Ilmiah Hukum dan Kenegaraan, 2025)
Purpose: The use of prohibited means in armed conflict aims to respect and uphold the principles of humanity and proportionality in International Humanitarian Law (IHL) and prevent unnecessary injuries. This study aims to determine Indonesia's international commitment to respecting the principles of IHL through Indonesia's participation in international agreements on the prohibition of the use of certain weapons. Methodology/approach: This study implements a normative method by analyzing Indonesia's participation in international agreements related to the use of prohibited weapons during times of conflict. Results/findings: This study found that Indonesia's participation in these agreements is low, which has an impact on the few national regulations governing the prohibition of the use of prohibited means during times of conflict. Conclusion: Indonesia needs to strengthen its commitment to the principles of humanity and proportionality under international humanitarian law by ratifying legal instruments prohibiting certain weapons. This step should be accompanied by internal military policies and official political statements demonstrating respect for humanitarian law, both in written and customary international law. Limitations: This research is limited to inventorying Indonesia's participation in international agreements related to the prohibition of the use of certain means in armed conflict. Contribution: This research is expected to be a reference for investigating national laws or actions of the Indonesian Government regarding the prohibition of the use of certain weapons in armed conflict.